Options for the diagnosis of high blood pressure in primary care: a systematic review and economic model - Constanti, M; Boffa, R; Floyd, CN; Wierzbicki, AS; McManus, RJ; Glover, M (Springer Nature, 2020)
The 2011 NICE hypertension guideline (CG127) undertook a systematic review of the diagnostic accuracy of different blood pressure (BP) assessment methods to confirm the diagnosis of hypertension. The guideline also undertook a cost–utility analysis exploring the cost-effectiveness of the monitoring methods. A new systematic review was undertaken as part of the 2019 NICE hypertension guideline update (NG136). BP monitoring methods compared included Ambulatory BP, Clinic BP and Home BP. Ambulatory BP was the reference standard. The economic model from the 2011 guideline was updated with this new accuracy data. Home BP was more sensitive and specific than Clinic BP. Specificity improved more than sensitivity since the 2011 review. A higher specificity translates into fewer people requiring unnecessary treatment. A key interest was to compare Home BP and Ambulatory BP, and whether any improvement in Home BP accuracy would change the model results. Ambulatory BP remained the most cost-effective option in all age and sex subgroups. In all subgroups, Ambulatory BP was associated with lower costs than Clinic BP and Home BP. In all except one subgroup (females aged 40), Ambulatory BP was dominant. However, Ambulatory BP remained the most cost-effective option in 40-year-old females as the incremental cost-effectiveness ratio for Home BP versus Ambulatory BP was above the NICE £20,000 threshold. The new systematic review showed that the accuracy of both Clinic BP and Home BP has increased. However, Ambulatory BP remains the most cost-effective option to confirm a diagnosis of hypertension in all subgroups evaluated.